Gambaran Status Hemodinamik Sebelum dan Sesudah Injeksi Spinal Anestesi Pada Pasien Transurethal Resection of The Prostate di RSI Purwokerto - Rumadan, Elsafika; Susanto, Amin; Sebayang, Septian Mixrova (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Transurethral Resection of the Prostate (TURP) is a common surgical intervention for patients with benign prostatic hyperplasia. Spinal anesthesia is the preferred technique for TURP but carries a primary risk of hypotension. This study aims to describe the hemodynamic status before and after spinal anesthesia injection in TURP patients and to present general patient characteristics such as age and physical status according to the American Society of Anesthesiologists (ASA). This descriptive quantitative study uses a cross-sectional approach. Data were collected from 30 patients undergoing TURP with spinal anesthesia, observing hemodynamic changes before and after spinal anesthesia injection. The results showed that the majority of respondents were aged 55-64 years (56.7%) and had an ASA physical status of 1 (53.0%). Before spinal anesthesia, 36.7% of patients were hypertensive, and 63.3% were normal. All patients had normal pulse, oxygen saturation, respiration, and body temperature before spinal anesthesia. At the 5th minute after spinal anesthesia, 96.7% of patients experienced hypotension, all patients maintained normal pulse, oxygen saturation, and respiration, but 23.3% of patients experienced hypothermia. In conclusion, spinal anesthesia in TURP patients causes significant hemodynamic changes in blood pressure, with the majority of patients experiencing hypotension. Pulse, oxygen saturation, and respiration remained stable, while body temperature decreased in some patients. These findings highlight the importance of proper monitoring and management to anticipate hemodynamic complications during TURP procedures.